Penta Helix Model: Developing Economic Potential Through Halal Tourism And Local Cuisine Padangsidempuan City - Mery Octavianna Lubis, Rizky; Maya Mei Shanty, Ade (SEAN Institute, 2024)
Tourism acknowledges the growing interest in Halal tourism, both from an industry and research. Regional wisdom is needed to approach development holistically to achieve equitable progress in economic, ecological, and social justice aspects. To enhance tourism growth, several elements must collaborate with stakeholders, a concept known as the